Analysis of Character Value Content in Folk Stories in Student Thematic Books - Irfan, Muhammad (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to determine the distribution of religious values in thematic short stories for class VI theme 8. Methodology: This research method is qualitative with content analysis. The instrument used was short story books in thematic textbooks for class VI theme 8. This study concludes that several character values are contained in folklore in thematic books for class VI students theme 8. Main Findings: The results of this study are character values include religious, tolerant, friendly, peace-loving, social care, hard work, and responsibility. Responsibility is a charge that dominates character values. By instilling the value of responsibility to students, it is hoped that it can provide various benefits and shape the attitudes, behavior and character of students. Novelty/Originality of this study: Based on the directives from the ministry of Education that each lesson must integrate each character so that students can develop their character